Equivalent energy-level structures in stacked metamaterials. Issue 45 (3rd November 2015) - Liu, Chuanbao; Bai, Yang; Zhou, Ji; Zhao, Qian; Yan, Yu; Li, Jinxu; Su, Yanjing; Qiao, Lijie
Abstract : For stacked metamaterials, meta-atoms act as real atoms in nature materials, whose characteristic frequency bands behave as the equivalent energy levels. Abstract : The unusual properties of metamaterials originate from their artificial metallic structures; however, these materials indeed behave as an effective medium in the operating frequency range. Correspondingly, the unit cell is called a meta-atom, but its relationship with real atoms has not been substantially studied. In this paper, we studied a stacked fishnet metamaterial in the optical frequency range and established a basic relationship between the meta-atom and the real atom. The characteristic frequency of meta-atoms behaves just as the energy level of real atoms, which splits with the stacked meta-atom number, converges with the atom spacing and is sensitive to the features of the center dielectric layer. This work will increase the understanding of metamaterial physics in view of solid-state physics and guide metamaterial design through quantum mechanical methods.